Synthesis of Thia(oxa)zolopyridines and Their Inhibitory Activities for beta-Amyloid Fibrillization - Lee, Yeo Ran; Kim, Dong Jin; Mook-Jung, Inhee; Yoo, Kyung Ho (WILEY-V C H VERLAG GMBH, 2008)
A series of thiazolo[5,4-b]pydine and oxazolo[5,4-b]pyridine derivatives 1a-o were designed. These fifteen compounds were evaluated by A/beta 42 fibril formation inhibitory assay using thioflavin T as a dye. Thiazolo[5,4-b]pyridines 1a-g showed potent inhibitory activities for A beta 42 fibrillization at IC50 of 0.23-4.5 mu M. Among them, compounds 1b and 1k having methoxy group at C-5 exhibited excellent activities (IC50 = 0.23 and 0.50 mu M, respectively) than that of Curcumin (IC50 = 0.80 mu M).
Keywords: ALZHEIMERS-DISEASE; FIBRIL FORMATION; PROTEIN; PLAQUES; CYCLIZATION